Dental caries and treatment needs in 12-year-old schoolchildren from public schools of the municipality of Rionegro (Antioquia, Colombia), 2010 - Vivares-Builes, Annie M.; Saldarriaga-Saldarriaga, Andrés F.; Muñoz-Pino, Natalia; Miranda-Galvis, Marisol; Colorado-Colorado, Kelly; Montoya-Zuluaga, Yenny P.; Viñas-Sarmiento, Yomaira; Agudelo-Suárez, Andrés A. (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: analyzing dental caries conditions of 12-year-old population allows verifying how much of the oralhealth related goals have been achieved. The objective of this study was to describe the experience and prevalence of dental caries and treatment needs of 12-year-old school children in the municipality of Rionegro. Methods: this was a cross-sectional descriptive study on 808 schoolchildren aged 12 years from public schools of the municipality of Rionegro. Both traditional (T) and modified (M) decayed, missing and filled teeth indexes (DMFTT and DMFTM) were used, as well as the Significant Caries Index (SiC). The obtained data were analyzed according to gender, education level, place of residence, and health insurance status. Results: the DMFTT value among the studied population was 1.70 (± 1.63) and the DMFTM was 2.19 (± 1.92). The prevalence of cavitated caries lesions was 59.9%, and for all the lesions it was 70.8%. Caries experience for the DMFTT was 69.9%, and 77.8% in the case of DM TM. The SiC measured according to the DMFTT was 3.60, and 4.42 for DMFTM. Significant differences were observed in terms of experience, prevalence and treatment needs, especially in relation to gender and school grade. Conclusions: these values indicate accomplishment of the goals set by the WHO and by Colombian standards. Nevertheless, they also reveal some inequalities that must be considered when planning promotion, prevention and attention programs aimed at this population.